Efek dari Kombinasi Pupuk N, P dan K terhadap Pertumbuhan dan Hasil Kacang Tanah pada Lahan Kering Alfisol - Suryono Suryono; Sudadi Sudadi (Universitas Sebelas Maret, 2015)
This study was aimed to determine the effect of fertilizer dose combination of N, P, and K on growth and yield of peanut on Alfisols dryland. The experiment was conducted from April to September 2014 in Sukosari Village, Jumantono, Karanganyar with 3 factor completely randomized design arranged N (Urea) fertilizer dose (50,100,150) kg ha-1, P (SP-36) fertilizer dose (100,200,300) kg ha-1 and K (ZK) fertilizer dose (75,150,225) kg ha-1. Statistical analysis using F test 5% followed by DMRT with 95% confidence level. The parameters observed were wet and dry weight of plant per sample, number of filled pods per sample, weight of pods per sample, and weight of dry seed per sample. Fertilizer dose combination of N, P and K significantly affect on dry weight. Fertilizer dose combination N and P significantly affect on number of filled pods and weight of pods per sample. Combination of P and K fertilizers significantly affect on dry seed weight. N fertilizer dose significantly affect on weight of dry seed per sample. The best fertilizer dose combination is P3K3 treatment (300 kg ha-1 and 225 kg ha-1) that can increased 57 % weight of dry seed if compared with recommendation dose.